Geologia e Geoquímica do Stock Serra das Intãs, Sistema Orogênico Sergipano, NE Brasil - Teles, Danilo dos Santos (2019)
The Serra das Intãs Stock (SSI) is a 5 km2 stock with an ellipsoid shape, with a NW- SE orientation that occupies the axial region of a synform located between the municipalities of Gararu and Porto da Folha. This stock is intrusive in the metasediments of the Macururé Group of the Sergipano Orogenic System. The SSI is composed of muscovite biotite monzogranites, holeucocratic of whitish gray colors, medium to fine granulation, equigranular texture, locally with gneiss structure. Biotite is the mafic mineral in these rocks and the muscovite is associated with biotite, these micas include subhedral crystals of apatite, titanite and zircon. Chemical analysis of feldspar and biotite allowed to identify the composition of plagioclase crystals as having normal compositional zonation, varying from albite (An2-10%) to oligoclase (An10,1-15,4%) and alkali feldspar (Or91-94 , 5% Ab5.4- 9.7%). The chemical data of biotite crystals allowed to classify them as Fe-biotite, rebalanced primers associated with orogenic calciumalkaline magmas. The rocks are peraluminous to metalluminous, and have affinities with the calcium-alkaline series of high potassium and shoshonítica, that stand in the field of the cordilleran magnesian granites. They present enrichment of LILEs in relation to HFSE, with valleys pronounced in Nb, Ta, P and Ti; and have enrichment of the LREE in relation to the HREE, with weak negative anomalies in Eu. The geochemical signature of the SSI is compatible with syn-collisional granites of arc environment.